AMIR TEMUR'S STRUGGLE AGAINST THE MONGOLS AND THE CONQUEST OF TRANSOXIANA - Student Saydullayeva Aynura (Western European Studies, 2025)
This article explores Amir Temur’s struggle against the Mongols and his conquest of Transoxiana. It analyzes the historical context of his rise to power, his military strategies against the Chagatai khans, and the significance of these events in consolidating his state
Keywords: Amir Temur; Mongols; Chagatai